Kasaysayan at vulnerabilidad ang lipunang Pilipino sa harap ng pananalanta ng pesteng balang, 1569-1949 - Juan , Ma. Florina Orillos (Manila De La Salle University Publishing House, 2017)
Filipino society in the midst of locusts epidemic between 1569 and 1949 in the Philippines.
In Tagalog.
Keywords: Locusts -- Philippines -- History; Agricultural pests -- Philippines -- History; Philippines -- Rural conditions